RANCANG BANGUN BRACKET PLATFORM PADA MESIN WELD MANIPULATOR - Irawan, Benny Haddli; Cahyagi, Danang; Alwi, Abdullah; Hakim, Rahman (Politeknik Negeri Batam, 2025)
A welding manipulator is a specialist apparatus engineered for welding extensive and elongated pipe plates on both interior and exterior surfaces, as well as in vertical and horizontal positions. During the assembly process, a challenge occurs when the platform is excessively distanced from the nozzle, complicating the operator's task with the welding manipulator. Brackets are an effective option to mitigate hazards and address issues throughout the cutting process. The aim of this research is to design and evaluate the safety of the bracket utilized for the platform component of the welding manipulator. The research utilizes Finite Element Analysis (FEA) to assess the simulated values of the safety factor and stress distribution. The findings demonstrate that the bracket design satisfies strength criteria, producing a maximum stress value of 98,327,504.00 N/mÂ². The recorded maximum displacement is 1.094 mm, and the maximum strain is 0.00022. The computed safety factor is 2.1, indicating that the design parameters surpass established safety criteria.